20.0k views
3 votes
ANY JESUS HELPERS PLEASE HELP The incorrect work of a student to solve an equation 2(y + 4) = 4y is shown below: Step 1: 2(y + 4) = 4y Step 2: 2y + 6 = 4y Step 3: 2y = 6 Step 4: y = 3 Which of the following explains how to correct Step 2 and shows the correct value of y? The equation should be y + 4 = 4y after division by 2; y = 5 The equation should be y + 4 = 4y after division by 2; y = 2 2 should be distributed as 2y + 8; y = 4 2 should be distributed as 2y + 8; y = 2

User Modeller
by
5.0k points

2 Answers

2 votes

Answer:

2 should be distributed as 2y + 8; y = 4

Explanation:

Step 2 is wrong.

2(y + 4) = 4y

The step to solve is to expand brackets or distribute 2, not divide both sides by 2.

2y + 8 = 4y

Subtract both sides by 2y.

8 = 2y

Divide both sides by 2.

4 = y

User Edn
by
5.4k points
3 votes

Answer:

2 should be distributed as 2y + 8; y = 4

Explanation:

2(y + 4) = 4y

Distribute

2y + 8 = 4y

Step 2 is incorrect because the added instead of multiplied

Continuing on to correct the problem

Subtract 2y from each side

2y+8-2y = 4y-2y

8 = 2y

Divide by 2

8/2 = 2y/2

4 =y

User NSSec
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.